The applications of single‐atom alloys in electrocatalysis: Progress and challenges. Issue 1 (18th July 2022) - Da, Yumin; Jiang, Rui; Tian, Zhangliu; Han, Xiaopeng; Chen, Wei; Hu, Wenbin
Abstract: The development of cost‐effective and highly efficient electrocatalysts to accelerate distinct electrochemical reactions is essential to help the industry to achieve a low‐carbon footprint. Single‐atom alloys (SAAs) with the characteristics of unique electronic structures, well‐defined active sites, and maximum atom utilization demonstrate promising potential to replace traditional noble metal catalysts. SAAs are expected to tailor the adsorption properties of reaction species, thus promoting electrocatalytic behaviors. Herein, representative synthetic strategies including wet chemistry, galvanic replacement, dealloying, and atomic layer deposition are introduced, followed by a summary of applications of SAAs in hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, carbon dioxide reduction reaction, and ethanol electro‐oxidation to provide an in‐depth understanding of the structure–activity relationship. Moreover, the challenges and perspectives in this emerging field of SAAs are discussed. Abstract : Single‐atom alloys (SAAs) with peculiar electronic structures, well‐defined active sites, and maximum atom utilization are promising to replace traditional noble metal electrocatalysts. Representative strategies to prepare SAAs including wet chemistry, galvanic replacement, dealloying, and atomic layer deposition are introduced. Electrocatalytic applications including hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, carbon dioxide reduction reaction, and ethanol electro‐oxidation of SAAs are summarized to gain an in‐depth understanding of the catalytic mechanism.